Patterns of disease relapse in primary extremity soft‐tissue sarcoma. Issue 11 (9th August 2016) - Smith, H. G.; Memos, N.; Thomas, J. M.; Smith, M. J. F.; Strauss, D. C.; Hayes, A. J.
Abstract: Background: Extremity soft‐tissue sarcomas comprise a range of distinct histological subtypes. This study aimed to characterize the patterns of disease relapse in patients undergoing resection of primary extremity soft‐tissue sarcoma. Methods: All patients who had resection of primary extremity soft‐tissue sarcoma at the Royal Marsden Hospital between January 2004 and January 2014 were identified from an institutional database. Results: In the period examined, 556 patients underwent resection. The most common histological subtypes were undifferentiated pleomorphic sarcoma (169 patients, 30·4 per cent), well differentiated liposarcoma (63, 11·3 per cent), myxoid liposarcoma (62, 11·2 per cent), myxofibrosarcoma (54, 9·7 per cent) and leiomyosarcoma (39, 7·0 per cent). Local recurrence‐free survival (LRFS) did not differ significantly between histological subtypes ( P = 0·222). Distant metastasis‐free survival (DMFS) and disease‐specific survival (DSS) were found to differ significantly between subtypes ( P < 0·001 for both DMFS and DSS), with the worst outcomes in patients with undifferentiated pleomorphic sarcoma (5‐year survival rate: 56·8 (95 per cent c.i. 52·5 to 61·1) per cent for DMFS; 60·1 (55·6 to 64·6) per cent for DSS). However, on multivariable analysis, histological subtype was not found to be independently prognostic for LRFS, DMFS or DSS. Metastatic disease developed in 149 patients, with the lungs being the most common site of first metastasis (120 patients, 80·5 per cent). The site of first metastasis differed between subtypes, with extrapulmonary metastases predominant in myxoid liposarcoma (11 of 13 patients; P < 0·001). Conclusion: Although histological subtype was not found to be an independent prognostic factor for oncological outcomes, the site of first metastasis differed significantly between subtypes. Abstract : Subtype matters for follow‐up